(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article classifies the general mechanisms of providing qualified psychological services to military personnel who are in need of psychological help as a result of various social factors. Providing psychological support to military personnel who are under mental stress at work, the process of understanding the events after the effects of the stressful situation have ended, and various methods of providing them with psychological support are explained. The article provides an overview of approaches, theories, and controversial issues and problems related to psychological care. The concept of mental exhaustion is revealed in connection with semantic concepts such as trauma, stress, loss, transit.